2018
DOI: 10.3168/jds.2017-14270
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of orally administered anti-IL-10 antibody in milk-fed dairy calves

Abstract: The primary objective of this randomized controlled trial was to determine whether anti-IL-10 egg yolk antibodies fed upon arrival to a calf ranch would lower the prevalence of Cryptosporidium parvum shedding in naturally challenged preweaned dairy calves. The secondary objectives included measuring the effect of anti-IL-10 antibodies on calf health, performance, and shedding of less common diarrheal pathogens. A total of 133 calves, enrolled at 24 to 72 h of age, received a daily dose of 0.96 g of egg yolk po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The current study also demonstrated dietary SID M+C levels had no effects on intestinal luminal levels of IL-10, an immune suppression cytokine that may thwart the development of host immunity against viruses, bacteria and helminths (Collier et al, 2008 ; Cyktor and Joanne, 2011 ). We have previously shown that an oral antibody to IL-10 can reduce the growth suppression caused by Eimeria infection (Arendt et al, 2016 ; Sand et al, 2016 ; Raabis et al, 2018 ). The current results indicate that IL-10 is not involved in the sulfur amino acids-derived effects on growth performance and intestinal anti- Eimeria IgA concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The current study also demonstrated dietary SID M+C levels had no effects on intestinal luminal levels of IL-10, an immune suppression cytokine that may thwart the development of host immunity against viruses, bacteria and helminths (Collier et al, 2008 ; Cyktor and Joanne, 2011 ). We have previously shown that an oral antibody to IL-10 can reduce the growth suppression caused by Eimeria infection (Arendt et al, 2016 ; Sand et al, 2016 ; Raabis et al, 2018 ). The current results indicate that IL-10 is not involved in the sulfur amino acids-derived effects on growth performance and intestinal anti- Eimeria IgA concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…So it would be interesting to investigate the underlining mechanism of how the serum sodium may induce the COVID-19 severeness. The feature “Urine | PH(Urine)” is the pH level in the urine, and quite a few investigations observed the aberrant pH levels in the body fluid or fecal matter of the coronavirus-infected animals [54,55]. Although the urine pH level was not investigated in the coronavirus-infected animals, this may be worth of an investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the IL-10 level may be due to the decrease of parasite load in the intestine. The recovery from C. parvum was reported to be associated with the downregulation of IL-10 levels, as prolonged IL-10 production leads to a slow recovery rate [70, 71]. Hence, the present result may suggest that both a Th1 and a Th2 immune response are essential for effective control the C. parvum infection, with the Th1 response occurring first, followed by a balanced Th1 and Th2 response.…”
Section: Resultsmentioning
confidence: 65%